2019
DOI: 10.1007/s12039-019-1711-9
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-catalyzed synthesis of C4-chalcogenoalkylated oxindoles via Sommelet-Hauser type rearrangement of 3-diazoindolin-2-ones

Abstract: Efficient rhodium-catalyzed Sommelet-Hauser type rearrangement of 3-diazoindolin-2-ones with a-thioesters has been accomplished for the synthesis of C4-thioalkylated oxindoles. The developed reaction offers the selective functionalization of C4-position of oxindole via generation of S-ylide and [2, 3]-sigmatropic rearrangement and allows access to diverse C4-thioalkylated oxindoles in good to excellent yield. Furthermore, the method was successfully extended to the synthesis C4-selenoalkylated oxindoles employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Later, we demonstrated the rhodium-catalyzed Sommelet-Hauser rearrangement in the diazo compounds 31 derived from isatin and exclusive formation of Sommelet-Hauser rearrangement product 33 was observed (Scheme 6). [16] This methodology showcases the selective synthesis of C4-thioalkylated 33 a and C4-selenoalkylated 33 b-c oxindoles with good yields from the corresponding α-thio-and α-selenoesters 32…”
Section: Dongari Yadagiri Was Born Inmentioning
confidence: 96%
“…Later, we demonstrated the rhodium-catalyzed Sommelet-Hauser rearrangement in the diazo compounds 31 derived from isatin and exclusive formation of Sommelet-Hauser rearrangement product 33 was observed (Scheme 6). [16] This methodology showcases the selective synthesis of C4-thioalkylated 33 a and C4-selenoalkylated 33 b-c oxindoles with good yields from the corresponding α-thio-and α-selenoesters 32…”
Section: Dongari Yadagiri Was Born Inmentioning
confidence: 96%
“…7). 15 Sulfonium ylides generated from 3-diazoindolin-2-one 38 and α-thioester 39 under rhodium-catalyzed conditions underwent a [2,3]-rearrangement to provide 4-substituted oxindole 41. The method was Fig.…”
Section: Review Organic and Biomolecular Chemistrymentioning
confidence: 99%
“…7). 15 Sulfonium ylides generated from 3-diazoindolin-2-one 38 and α-thioester 39 under rhodium-catalyzed conditions underwent a [2,3]-rearrangement to provide 4-substituted oxindole 41 . The method was also extended to α-selenoesters 40 to access the corresponding 4-selenoalkylated oxindoles via Sommelet–Hauser rearrangement of selenonium ylides.…”
Section: Sulfonium Ylidesmentioning
confidence: 99%
“…17 In 2019, Anbarasan et al developed a Rh-catalysed Sommelet–Hauser-type rearrangement of 3-diazoindolin-2-ones with α-thioesters. 18 Wang and co-workers demonstrated the synthesis of isatin-hydrazones from 3-diazooxindoles and sulfoxonium ylides. 19 Then, a one-pot procedure to synthesize functionalized 3-indolylindolin-2-ones, 3-(1-methylpyrrol-2-yl)indolin-2-ones, and 3-(thiophen-2-yl)indolin-2-ones via indium( iii )-catalysed reaction of various 3-diazoindolin-2-ones with indoles, 1-methylpyrrole, or thiophene was developed by Lee et al 20 Shi and collaborators reported a Rh-catalysed reaction of 3-diazooxindoles with indoles and isatin-derived ketimines to generate 3,3′,3′′-trisindoles (Scheme 1e).…”
Section: Introductionmentioning
confidence: 99%